Legitimacy and legitimation of the Russian public authority - D. A. Avdeev (Правоприменение, 2021)
The subject. The article is devoted to the legal analysis of the legitimacy of the activities of public authorities and the process of their legitimation in the Russian Federation, as well as other problems of national democracy. The legal understanding of the concept of "people" as the only source of power and the bearer of sovereignty is considered, a distinction is made between these properties.The purpose of the article is to identify its essential features the category of legitimacy, identify problems related to the reflection of the political will of Russian citizens in the organization and activities of state authorities and local self-government. The purpose of the article is to substantiate also the differences in the characteristics of the people as the only source of power and the bearer of sovereignty, which has a significant impact on the processes of legitimation of public authorities in the Russian Federation.The research methodology consists of general scientific methods (analysis, synthesis, dialectics) and legal methods (formal-logical, comparative-legal, historical-legal, forecasting method).The main results and their area of application. The author considers legitimacy not only as the consent of the people with the normative legal acts adopted by public authorities, but also as universal approval and recognition of their organizational activities, expressed by citizens through the institutions of direct democracy. The legitimacy of public authority is an attribute of a constitutional state with a social orientation. The article notes a few features characteristic of the domestic process of legitimizing public authority. The procedure for the formation of the Federation Council of the Federal Assembly, in which Russian citizens do not participate directly, starting from 1995 to the present. The cancellation and return of direct elections of heads of constituent entities of the Russian Federation, the impossibility of electing the heads of municipalities directly by the population (in many cases). A complicated procedure for the implementation of active and passive electoral rights in the Russian Federation, expressed in the establishment of several formal require ments. Constant changes in electoral legislation before election campaigns are among these characteristics.Conclusions. The results of research are summarized and conclusions are drawn about the current state of legitimacy in the Russian Federation. A few measures are proposed to improve the process of legitimizing public authority. The author proposes to distinguish between the legal characteristics of the people as the bearer of sovereignty, understanding by it all Russian citizens and as the only source of power, which is formed by the voters.